PERAN PELATIHAN PENGUATAN TOLERANSI SOSIAL DALAM PEMBELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN DI SEKOLAH MENENGAH PERTAMA - Japar, Muhammad; Irawaty, Irawaty; Fadhillah, Dini Nur (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2019)
The results of observations in several junior high schools in Jakarta showed that in the current global era the presence of millennial generation cultural values, a person needs a strong controller to be able to choose and sort out the values freely offered. That is necessary to strengthen social tolerance, especially for teachers in Junior High School. The activity was carried out in order to establish a tolerant attitude, especially in instilling multicultural values such as democracy, justice, equality, tolerance and respect for diversity. As well as improving the ability of teachers to provide reinforcement of social tolerance in the learning of Civic Education in junior high school. The method used to strengthen social tolerance of Civic Education learning is through training that is guided by experienced instructors. The evaluation used to measure the success of this training can be seen through the training activity evaluation questionnaire that was filled in by all the training participants. The target audience for this training activity are Civic Education teachers in Junior High School at Jakarta. The results of this training show that in the cultivation of social tolerance there are several attitudes that must be taken, namely: Harmonious interaction, Instilling brotherhood, instilling caring attitude, Collaborative attitude. It is expected that the planting of social tolerance provided by Civic Education teacher to students can achieve Civic Education vision of building smart and good citizens. Furthermore, by cultivating sustainable tolerance it will build tolerant citizens. Because citizens who are intellectually intelligent, both emotionally and actively building a country for a better Indonesia.